Using Fixed Column Primer for Computation of Boolean Matrix Multiplication with DNA - Nordiana, Rajaee; Tay, Kai Meng; Asrani, Lit; Sharifah Masniah, Wan Masra (2011)
In our previous work, we implemented an in vitro implementation of Boolean matrix multiplication with DNA computing. However, with the increase in the problem size, the material consumption of DNA and the number of experimental steps required to compute the problem increases drastically. Thus in this paper, we introduce fixed column primer method to reduce the material consumption and the labour intensiveness of the computation.